Bead Board Letter Media Effectiveness as The Introduction Concept of Reading in Children Aged 5-6 Years - Juwita, Tusifa; Tasuah, Neneng (Indonesian Journal of Early Childhood Education Studies, 2015)
Introducing of reading concept is a process for introducing some words that doing by early introducing on alphabet symbol reading. A study of reading for early childhood is an important thing as preparation for reading readiness because it is the chance for kids as preparation for reading. One of the methods that given for introducing reading concept for kids is using attractive games and activities, such as alphabet beads board. The purpose of this research is for discover the effectivity of alphabet beads board as introducing of reading concept for kids age 5-6 years old (Experimental Research In Masyitoh V Margasari Kindergarten, Margasari District, Tegal County). This research using method Quasi-Experiment with The Static Group Comparison. Sampling technique is using Cluster Sampling with 5th Masyitoh Margasari Kindergarten as the experimental group and Karang Asem Masyitoh Kindergarten as the control group. Homogeneity test (F) showing if test score of the control group and the experimental group has variance difference. Acquired F significant score as big as 0,666. Because the significant score > 0,05; they are 0,666 > 0,005; so H0 is refused. Hypothesis test using t-test estimate (Independent sample t-test) and acquired score as big as 13,599 with ttable score as big as 2,390. Because tcount score > ttable score, they are 13,599 > 2,390; so H0 is refused. That show if there are difference on average test score of introducing of reading concept for kids age 5-6 years old. The conclusion that acquired from this research is there are significant influence by using of alphabet beads board as media for introducing of reading concept on experimental group. The meaning of this research if the using of alphabet beads board is effective as media for introducing of reading concept for kindergarten kids age 5-6 years old. Researcher suggests if we should be give learning process that proper with the personal context of early childhood by using applying and developing for enjoyable, simple, and easy media with some variation and innovative activities. How to cite Juwita, T., & Tasu’ah, N. (2015). Bead Board Letter Media Effectiveness as The Introduction Concept of Reading in Children Aged 5-6 Years. Indonesian Journal Of Early Childhood Education Studies, 4(1), 46-50. doi:10.15294/ijeces.v4i1.9453